Sap Beetle (Coleoptera: Nitidulidae) Management in Strawberries - Silvia I. Rondon; James F. Price; Daniel J. Cantliffe (EDIS, 2004)
Sap beetles (Coleoptera: Nitidulidae) are conspicuous arthropods that feed on flowers, fruits, sap, fungi, stored products, decaying and fermenting plant tissues from diverse trees and crops, including strawberries. Sap beetles work in association with yeasts and other fungi causing the fermentation of infested plant parts (Fig. 1). They also are known to transport a variety of microorganisms that cause plant diseases; a few species can behave as predators of various ornamental pests (Dowd, 1991; Dowd and Weber, 1991). Sap beetles are often considered minor pests; however, their main impact is due to the contamination of products caused by adults and larvae. This document is HS993, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: October 2004.